Autophagic-active nanosystem for senile bone regeneration by in-situ mitochondrial biogenesis and intercellular transfer - Meihua Zhang; Xiaoqing Sun; Ming Lu; Xingyou Wang; Shuyao Liu; Xiaoqin Hu; Jing He; Bin Luo; Yao Wu (Bioactive Materials)
Natural intercellular mitochondrial transfer has been recognized as a pivotal mechanism in the treatment of various diseases. Bone marrow mesenchymal stem cells (BMSCs), owing to their low bioenergetic demands and inherent homing capacity, are considered highly promising mitochondrial donor cells. However, this strategy is limited in senile osteoporosis (SOP) because large amounts of ROS produced by mitochondrial oxidative stress in senescent BMSCs (S-BMSCs) impairs their viability and function. Here, we report that in-situ treatment of senescent bone marrow-derived macrophages (S-BMDMs) with a cerium-based nanosystem (CNS) composed of antioxidant and energy-active units, which exhibits superior autophagy-activating capability, effectively restores the viability and osteogenic function of S-BMSCs by promoting mitochondrial biogenesis and transfer. Transcriptomic profiling revealed that the SIRT1-PGC-1α axis, significantly associated with autophagy activation, drives mitochondrial biogenesis in S-BMDMs. The efficient intercellular mitochondrial transfer ameliorates the senescent bone microenvironment, rescues S-BMSCs functionality, and enhances bone formation. In conclusion, the autophagy-activating CNS, by effectively rejuvenating S-BMDMs and promoting mitochondrial biogenesis and transfer, provides an innovative therapeutic strategy for SOP-associated bone regeneration.